Isolation and characterisation of antifungal compounds from medicinal plants that are active against selected fusarium species - Seepe, Hlabana Alfred (My University, 2021)
Fusarium species are among pathogenic organisms responsible for massive yield and quality losses in crop production. They cause crop diseases in the field and during storage, and some species are capable of producing mycotoxins which contaminate products and threaten consumer s’ health. Conventional synthetic fungicides are available for the control of Fusarium pathogens, however, their applications have been restricted or discouraged due to their harmful effect on the environment, livestocks and human health. There are also reports about fungal-resistance to available fungicides. Moreover, the synthetic chemicals are not affordable to smallholder farmers and to some extent, they are not recommended for applications in organic farming. As an alternative to these fungicides, selected medicinal plant species were investigated as sources of natural chemicals or compounds with potential to be developed into plant-based fungicides to control Fusarium pathogens. This study aimed to identify antifungal extracts among the selected medicinal plant species which could be used to develop plant-based fungicides to control Fusarium diseases. It also focused on isolation and characterization of antifungal compounds from selected medicinal plant species. Thirteen medicinal plant species (Combretum erythrophyllum (Burch.) Sond , Melia azedarach L, Solanum mauritianum Scop, Nicotiana glauca Graham, Schotia brachypetala Sond, Lantana camara L, Combretum molle R. Br. ex G. Don, Quercus acutissima Carruth, Olea europaea L, Vangueria infausta Burch, Withania somnifera (L.) Dunal, Harpephyllum caffrum Bernh and Senna didymobotrya (Fresen.) H.S. Irwin & Barneby) were selected from literature based on their reported strong antimicrobial activity against human and/or animal pathogens. The leaves of these plant species were collected, shade-dried and extracted with water, petroleum ether, ethyl acetate and acetone. Extractant yield was recorded and each extract was evaluated for antifungal activity using a micro-dilution assay against nine Fusarium pathogens (Fusarium verticillioides, Fusarium proliferatum, Fusarium subglutinans, Fusarium graminearum, Fusarium solani, xxvii Fusarium oxysporum, Fusarium semitectum, Fusarium chlamydosporum and Fusarium equiseti). Similar solvent extracts from different plant species that demonstrated MIC value of less than 0.1 mg/ml against the same pathogen were combined and evaluated for antifungal activity. The interation effect of combined extracts was determined by calculating their fractional inhibitory concentration index (FICI) in order to determine their possible synergistic, additive, indifference or antagonistic antifungal activity against tested pathogens. Plant extracts demonstrating synergistic and or additive interaction were further evaluated in combination and individually for in vivo antifungal activity against maize seed Fusarium pathogens. At least, one of the extracts obtained from these medicinal plant species showed strong antifungal activity with minimum inhibitory concentration (MIC) of less than 0.1 mg/ml against at least one of the tested pathogens. Of the four solvent extracts evaluated, acetone and ethyl acetate extracts showed stronger antifungal activity compared to petroleum ether and water extracts. Of the nine pathogens tested, F. proliferatum was the most susceptible and was strongly inhibited (MIC < 0.1 mg/ml) by 41 plant extracts whilst F. equisite was found to be resistant with MIC < 0.1 mg/ml by only three plant extracts. In total, each pathogen was tested against 52 plant extracts. There were 17, 16 and 15 extracts from C. erythrophyllum, S. mauritianum and Q. acutissima, respectively, with MIC values less than 0.1 mg/ml. These species were the most active when tested individually. Schotia brachypetala was found to be the least active medicinal plant with only seven extracts demonstrating very strong activity (MIC < 0.1 mg/ml) against the tested pathogens. Minimum inhibitory dilution (MID) or total activity was also calculated and it was found that water and acetone extracts had the highest MID, followed by ethyl acetate extracts while petroleum ether extracts recorded the lowest. Of all plant extracts tested against the nine pathogens, 59 plant extracts demonstrated MID values of more than 1000 ml/g. Out of the 348 extract combinations evaluated, 116 and 87 extract combinations demonstrated synergistic and additive antifungal activity, respectively. The strongest activity xxviii recorded for the combined extracts resulted from synergistic interaction with MIC value of 0.001 mg/ml against F. proliferatum and F. verticilloides. Combined acetone extract of C. erythrophyllum and Q. acutissima was very active (95.75% inhibition) against F. verticilloides inoculated on maize seeds while individual preparation from M. azedarach acetone extract demonstrated 97.10% inhibition against F. proliferatum. The extracts showing good antifungal activity (≥ 50% inhibition) were further tested for phytotoxicity on maize seed germination and the lowest recorded seed germination was 86.25%, resulting from Q. acutissima ethyl acetate extract. Combined acetone extract of C. erythrophyllum and Q. acutissima did not significantly affect maize seedling growth when compared to negative control (water treatment). All plant extracts that showed strong activity (MIC < 0.1 mg/ml) when tested using micro-dilution assay were spotted on thin layer chromatography (TLC) bioautographic assay to establish and determine the number of active compounds or bands. The white spots observed on the chromatograms indicated the presence of antifungal compounds. Combretum erythrophyllum, W. somnifera and L. camara exhibited the presence of antifungal compounds against 7, 5 and 4 pathogens, respectively. Hence, these plant species were selected for isolation of antifungal compounds where open column chromatography and preparative TLC were used for compound purification. At least, three isolated fractions from the three plant species were found to be active (MIC values ranging from 0.0098 to 0.625 mg/ml) against more than five pathogens. The fractions were also found to contain different levels of phytochemicals such as glycosides, flavonoids, steroids, and terpernoids. The structures of isolated compounds or fractions were determined using nuclear magnetic resonance (NMR) and mass spectroscopic (MS) techniques. A mixture of apeginin (4′,5,7-trihydroxyflavone) and salvigenin (5-hydroxy-6,7,4'-trimethoxyflavone) isolated from the leaves of C. erythrophyllum showed strong antifungal activity (MIC values ranging from 0.01 mg/ml to 0.63 mg.ml) against 5 tested Fusarium pathogens. Also isolated from C. erythrophyllum was a derivative of maslinic acid and it has xxix shown antifungal activity with MIC values ranging from 0.08 mg/ml to 0.63 mg/ml against 6 tested pathogens. On the other hand, lantadene A (22- angeloyloxy-9-hydroxy-3-oxo-olean-12-en-28-oic acid), boswellic acid (11-keto-β-boswellic acid) and boswellic acid glycoside isolated from the leaves of Lantana camara showed good activity (MIC values ≤ 0.63 mg/ml) against one or more Fusarium pathogens. Withaferin A (4β,27-dihydroxy-1-oxo-5β,6β-epoxywitha-2-24-dienolide) glycoside isolated from the leaves of Withania somnifera showed antifungal activity with MIC value of 0.16 mg/ml against F. verticilloides. This study demonstrated potential applications of medicinal plant extracts as cheap, accessible and sustainable source of eco-friendly pesticides for fighting crop diseases in organic and smallholder farming. The extracts can be used as treatment agents to control maize seed spoilage during post-harvest storage. Additionally, characterised antifungals may serve as scaffold compounds during commercial synthesis of plant-based fungicides.
Thesis (Ph.D. (Chemistry)) -- University of Limpopo, 2021
Keywords: Fusarium species; Crop diseases; Fusarium pathogens; Fungicides; Antifungal agents; Plants -- Effect of fungicides on; Fusariosis; Fusarium; Medicinal plants